HYDROCEPHALUS ASSOCIATED WITH AGENESIS OF THE CORPUS CALLOSUM DIAGNOSED IN A 9-YEAR-OLD CHILD, ANÁPOLIS - GOIS (CIPEEX, 2022)
ABSTRACTTHE FOLLOWING STUDY AIMS TO REPORT A CASE OF HYDROCEPHALUS ASSOCIATED WITH AGENESIS OF CORPUS CALLOSUM DIAGNOSED IN A 9-YEAR-OLD CHILD WITH DELAYED NEUROPSYCHOMOTOR DEVELOPMENT IN ANNAPOLIS. IT UNDERSTANDS THAT AGENESIS OF THE CALLOUS BODY (ACC) IS AN ABNORMALITY THAT CAN AFFECT THIS STRUCTURE, AND IS THEN CHARACTERIZED BY THE COMPLETE OR PARTIAL ABSENCE OF NERVE FIBERS THAT MAKE UP THE CALLOUS BODY. IN ADDITION, THIS CONDITION MAY BE ASSOCIATED WITH OTHER COMORBIDITIES SUCH AS HYDROCEPHALUS, WHICH HAS ITS ORIGIN IN DISTURBANCES OF THE BALANCE BETWEEN THE PRODUCTION AND ABSORPTION OF CEREBROSPINAL FLUID, WITH ITS ACCUMULATION IN THE VENTRICLES, WHICH RESULTS IN INCREASED INTRACRANIAL PRESSURE. THUS, THE CASE REPORTS THE HISTORY OF A MALE PATIENT, CURRENTLY 15 YEARS OLD, DIAGNOSED WITH HYDROCEPHALUS AND VALVE PLACEMENT FOR TREATMENT, WITH NEUROPSYCHOMOTOR RETARDATION, SPEAKING AND WALKING ONLY AT 4 YEARS. CURRENTLY, THE PATIENT RECEIVES ASSISTANCE FROM VARIOUS MEDICAL SPECIALTIES, MAKING THE USE OF MEDICATION, USES A WHEELCHAIR AND IS UNDER EVALUATION FOR VALVE REPLACEMENT. IN ADDITION, HE UNDERWENT A SERIES OF TESTS AND WAS DIAGNOSED WITH HYDROCEPHALUS AND CALLOSUS BODY AGENESIS, HOWEVER, THE CASE LACKS SOME DATA DUE TO THE ILLEGIBILITY OF MEDICAL CALLIGRAPHY. THUS, BASED ON THE CASE PRESENTED AND IN THE LITERATURE, IT PERCEIVES THE LACK OF STUDY THAT SEEKS TO UNDERSTAND THE PARTICULARITIES OF THESE DISEASES, TESTS THAT ALLOW THE EARLY DIAGNOSIS OF AGENESIS OF THE CALLOUS BODY AND WHAT ARE THE BEST FORMS OF TREATMENT, AIMING FOR A GOOD PROGNOSIS.
Keywords: Hydrocephalus; Agenesis of Corpus Callosum; Child; Case Reports